2021
DOI: 10.33365/ji-mr.v2i1.1068
|View full text |Cite
|
Sign up to set email alerts
|

Digital Mathematics Learning Companion (Dmlc): Aplikasi Android Guru Pendamping Khusus Matematika Bagi Penyandang Tunanetra Berbasis Suara

Abstract: Based on Law no. 20 of 2003 education is the right of all Indonesian citizens, including persons with disabilities, especially in this article, namely people who are blind. The research objective is to develop technology-based teaching media for blind people. The learning media developed will help blind people learn mathematics independently like normal people in utilizing the sophistication of existing technology for independent learning. The application will be called Digital Mathematics Learning Companion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…In a more detailed explanation, learning media and materials in the form of audio with features such as text-to-speech, voice command, audio speed can help students with special needs, especially those with visual impairments. This has been proven in research by Rohaeti et al (2021) and Fatimah et al (2021). Both of these studies used similar features in developing learning models for visually impaired students.…”
Section: Results and Discussion Students' Perceptions Of Friendly Mat...mentioning
confidence: 69%
See 2 more Smart Citations
“…In a more detailed explanation, learning media and materials in the form of audio with features such as text-to-speech, voice command, audio speed can help students with special needs, especially those with visual impairments. This has been proven in research by Rohaeti et al (2021) and Fatimah et al (2021). Both of these studies used similar features in developing learning models for visually impaired students.…”
Section: Results and Discussion Students' Perceptions Of Friendly Mat...mentioning
confidence: 69%
“…First, 30 participants expected the learning media and materials to have features such as braille, sign language, subtitles, and/or closed captions. In research by Fatimah, et al (2021), it was shown that the use of braille in an app successfully improved the learning of visually impaired students. Then, 25 participants expressed how learning media and materials can be in the form of video and/or audio.…”
Section: Results and Discussion Students' Perceptions Of Friendly Mat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Perkembangan teknologi seharusnya memberikan solusi praktis bagi perkembangan media pembelajaran untuk penyandang tunanetra (Fatimah, Parinata, Efendy, & Santika, 2021). Dengan perekembangan teknologi yang semakin canggih harusnya memudahkan segala aktifitas penyandang disabilitas netra ini.…”
Section: Pendahuluanunclassified